Model-driven development of Web applications the AutoWeb system. - Fraternali, Piero (ACM transactions on information systems.)
This paper describes a methodology for the development of WWW applications and a tool environment specifically tailored for the methodology. The methodology and the development environment are based upon models and techniques already used in the hypermedia, information systems, and software engineering fields, adapted and blended in an original mix. The foundation of the proposal is the conceptual design of WWW applications, using HDM-lite, a notation for the specification of structure, navigation, and presentation semantics. The conceptual schema is then translated into a ?traditional? database schema, which describes both the organization of the content and the desired navigation and presentation features. The WWW pages can therefore be dynamically generated from the database content, following the navigation requests of the user. A CASE environment, called Autoweb System, offers a set of software tools, which assist the design and the execution of a WWW application, in all its different aspects, Real-life experiences of the use of the methodology and of the AutoWeb System in both the industrial and academic context are reported.